Comparative study of steel plate shear walls with different types of unbonded stiffeners. (August 2019) - Yu, Jin-Guang; Liu, Li-Ming; Li, Bo; Hao, Ji-Ping; Gao, Xi; Feng, Xiao-Tian
Abstract: This paper presents a comparative study of the steel plate shear walls (SPSWs) with different types of unbonded stiffeners. Multiple ribs and precast concrete panels are installed for restraining the out-of-plane deformation of steel plates. The effect of spacing of unbonded ribs on the behaviour of SPSWs is first investigated through a finite element analysis. Subsequently, three 1/3-scale one-bay, two-storey SPSW specimens, namely unstiffened SPSW (US-SPSW), partially restrained SPSW (PR-SPSW) and completely restrained SPSW (CR-SPSW), are tested under cyclic loading. Test results indicate that specimens PR-SPSW and CR-SPSW exhibit similar load-carrying capacity, energy dissipation capacity, and stiffness degradation. Out-of-plane deformations of infilled steel plates, inward deformation of columns, and rotation of beam-column connections in both specimens PR-SPSW and CR-SPSW are effectively restrained, which alleviates the pinching phenomenon of hysteretic curves and stiffness degradation. As compared to the complete restraints for steel plates, partial restraints can increase the buckling area of the infilled steel plates and subsequently enhance the ductility of SPSW structure. They can also convert the deformation mode of infilled steel panels from the high-wave-low order to the low-wave-high order. In general, specimen PR-SPSW stiffened by unbonded multiple ribs with an appropriate spacing shows the excellent structural behaviour and constructability. Highlights: Steel plate shear walls (SPSWs) with different types of stiffener is investigated. Use of multiple ribs and precast concrete panel enhances the performance of SPSWs. Both types of stiffener have the similar influence on loading capacity of SPSWs. Out-of-plane deformation of plate decreases as restraining stiffness increases. SPSWs with multiple ribs have the better structural behaviour and constructability.